Gerakan Feminisme Islam di Era Digital: Analisis Bibliometrik pada Database Demensions - Erusmiati Erusmiati; Busro Busro (Gunung Djati Conference Series, 2023)
Feminism is a social, political and ideological movement with the same goal, and in the digital era this movement is very important in people's lives to achieve common goals, the object of this research is feminism in the digital era such as the feminist movement in social media which easily spread outside by using this social media. The research method uses quantitative research methods to identify Islamic feminist movements in the digital era. Bibliometric analysis was used to review publications related to the research scope to identify research trends, concepts, and required keywords. This bibliometric study explores scientific literature, analyzes methodology and the Islamic feminist movement in the digital age. Experts use bibliometric maps to have a better understanding of a subject which in this case is femism.